x + y = 4
x - 2y = -5
If the first equation is multiplied by 2 and then the equations are added, the result is _____.
3x = 13
3x = 3
x = 3

x + y = 4 multiple 2 on both sides: 2x + 2y = 8 equation 1; x - 2y = -5 equation 2; Adding up equation 1 and equation 2, 3x = 3 x + y = 4, x - 2y = -5 If the first equation is multiplied by 2 and then the equations are added, the result is 3x = 3.

x + y = 4 multiple 2 on both sides: 2x + 2y = 8 equation 1; x - 2y = -5 equation 2; Adding up equation 1 and equation 2, 3x = 3 x + y = 4, x - 2y = -5 If the first equation is multiplied by 2 and then the equations are added, the result is 3x = 3.

For the following system, use the second equation to make a substitution for y in the first equation 3x + y = 2, y + 4 = 3x, the result is: 3x + 3x - 4 = 2.

Added 4/29/2014 8:55:10 PM

This answer has been confirmed as correct and helpful.

There are no comments.